RSIS Series on the 14th Malaysian General Election – Backflow of Chinese Voters : Real or Imagined? - Oh, Ei Sun (2018)
There has been talk of ethnic Chinese voter “backflow” to the ruling coalition in Malaysia. While this may be exaggerated, it remains to be seen if this month’s general election would lead to a more inclusive government.